Dielectric permittivity, polarizability and dipole moment of refrigerants R1234ze(E) and R1234yf determined using a microwave re-entrant cavity resonator. (January 2019) - Sampson, Catherine C.; Kamson, Mobolaji; Hopkins, Matthew G.; Stanwix, Paul L.; May, Eric F.
Highlights: Dielectric permittivities for HFOs R1234yf & R1234ze(E) measured with a re-entrant resonator. Data range from 248 to 365 K at pressures to 11 MPa for both gas and liquid phases. Correlations that represent measured permittivities within 0.05 over entire range are presented. Measured dipole moments about 12% smaller than predicted by molecular modelling. Significant molecular ordering in liquid phase inferred from Kirkwood g factors. Abstract: Dielectric permittivities ( ε r ) have been measured using a microwave re-entrant resonator at temperatures from (248 to 365) K and pressures up to 11 MPa for the alternative refrigerants 1, 3, 3, 3-tetrafluoropropene (R1234ze(E)) and 2, 3, 3, 3-tetrafluoropropene (R1234yf) in the liquid and vapour phases. Values of ε r were also measured for liquid CO2 at temperatures below 274 K, extending the data available for this fluid. Molecular polarizability, dipole moment, and the dielectric virial coefficients of each hydrofluoroolefin (HFO) refrigerant were determined by applying the dielectric virial expansion and Kirkwood equation to the measured permittivity data. The experimental results for the vapour phase lead to dipole moments with relative standard uncertainties around 5% that are in reasonable agreement with values from molecular modelling. The measured dipole moment for R1234ze(E) of 1.13 D is about 12% smaller than predicted, while the measured dipole moment for R1234yf of 2.24 D is about 11% smaller than predicted. In the compressed liquid region, the two refrigerants exhibited quite different dependencies on temperature and density. The polarizability of liquid R1234ze(E) could be predicted within 4.2% using the gas phase parameters (measured dipole moment and molecular polarizability). In contrast, the temperature dependence of the polarizability of R1234yf was twice as large in the liquid phase as in the gas phase. The density dependence of the polarizability for liquid R1234yf is at least 10 times that of liquid R1234ze(E). Liquid phase data were also used to estimate effective Kirkwood correlation factors, g, by assuming them to be temperature independent over the range of measurements. The results indicate g  ≈ 2.4 for R1234yf and g  ≈ 1.2 for R1234ze(E).